Mosquito borne diseases related knowledge, practice and behavior of people in rural and peri-urban areas of Eastern Nepal - Khanal, V K; Pyakurel, P; Uprety, S; Rayamajhi, R B; Gupta, P P; Ghimire, A; Singh, S B; Pokharel, P K; Budhathoki, S S (Health Renaissance, 2015)
Background: Mosquito borne diseases are major health problems in rural areas even after implementation of national Vector Borne Disease Control Programme in Nepal. The information on mosquito borne diseases related knowledge, practices and behavior of the people of rural and peri-urban areas of Nepal living in endemic areas are essential to develop behavioral change communication messages and for producing policy to prevent and control mosquito borne disease in the country. Objective: To assess knowledge, practices and behavior of the people living in rural and peri-urban areas regarding mosquito borne diseases. Methods: A cross-sectional study of 413 households was conducted from 10th March - 10th April, 2013 in Inaruwa municipality and Duhabi village of Sunsari District. Pre-tested semi-structured questionnaire were administered by face to face interview for data collection. Results: Ninety four percent responded, malaria was caused by mosquito but only 21% responded as dengue and Japanese encephalitis was caused by mosquito. Malaria and filariasis were considered fatal disease by 40%; however 20% had no idea about Japanese encephalitis and dengue. More than 70% respondent had perception that mosquito bites at night only. Although use of bed-net was found to be higher; only 2% had knowledge on insecticide impregnated bed-nets. 31% of respondents didn’t take medication during anti-filarial campaign supplied by government mainly due to side effects. It was observed that 61% respondents were unaware about the routine JE vaccination by Nepal government. Conclusion: Health education must be taken into account for communities in endemic areas to create awareness regarding prevention from mosquito borne diseases. Health Renaissance 2014;12(2): pp: 92-98